2021
DOI: 10.3390/admsci11020054
|View full text |Cite
|
Sign up to set email alerts
|

Family Firms and Innovation from Founder to Successor

Abstract: Several empirical investigations indicate that family firms are more innovative under the founding generation’s leadership and become less innovative in later stages, while others state the opposite. Within this debate, limited attention has been devoted to understanding how intra-family succession might be an opportunity to maintain or improve family firms’ innovativeness. This paper aims to explore how family firms’ innovativeness may evolve from the first to the second generation and understand which condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…, 2007; Cailluet et al. , 2018), yet there is a great deal of controversy in theory and practice (Cesaroni et al. , 2021; Miller and Le Breton-Miller, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2007; Cailluet et al. , 2018), yet there is a great deal of controversy in theory and practice (Cesaroni et al. , 2021; Miller and Le Breton-Miller, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…There is a relationship between innovation capabilities and socioemotional dimensions in family firms (Fitz-Koch and Nordqvist, 2017). The analysis of innovation in family firms is not only related to research and development and technological innovation, but also focused on all activities that enable firms to define and develop new products, services, and processes (Cesaroni et al. , 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to our expectations, we found that heir leaders involve their organisations more in instrumental CSR activities than founder leaders. This finding may suggest that, although heir leaders may be exposed to all aspects of CSR, heirs engage in CSR through available instrumental aspects, in this case, those related to the dimension of quality and R&D. According to a recent study on business succession and innovation processes [109], when the second generation takes over, family businesses can maintain the levels of innovation inherited from their predecessors, as long as the leaders behave as "catalysts of change". Therefore, it is possible to think that, in our case, the founding leaders have been able to pass on the legacy of instrumental CSR to the heir leaders through the transmission of family values [74].…”
Section: Discussionmentioning
confidence: 99%